Korelasi kadar glukosa saliva dengan kadar glukosa darah terhadap terjadinya kandidiasis oral pada penderita diabetes melitus (Correlation of salivary glucose level and blood glucose level with oral candidiasis in diabetes mellitus patient ) - Sumintarti Sumintarti; Fildzah Rahman (DiscoverSys Inc., 2015)
Diabetes mellitus (DM)is a disorder of carbohydrate metabolism which characterized by increased blood glucose level,which also increase the salivary glucose level. Glucose is a good medium for the growth of microorganisms includingC.albicans. One of the most common infections of the oral mucosa of patientswith DM is candidiasis. Chronic candidiasismay develop to be a malignancy. This study aimed to determine the correlation of salivary glucose levels with bloodglucose levels to the occurrence of oral candidiasis in patients with DM. Analytic observational study was carried outthrough the determination of blood glucose levels just by way of strip using a glucometer and salivary glucose levels with